Development of a chemistry laboratory mini-kit for grade 7 science instruction - Baltero, Kris D (University of the Philippines Visayas, 2014)
The study was conducted in order to develop a mini-kit composed of different laboratory set ups that is adequate and adoptable for Grade 7 Science instruction. The main goal was to develop an environmentally safe but complete set of materials that will suit with the K-12 Science Education Curriculum. The components of the Chemistry Laboratory Mini-kit were the manual of procedures with worktext, a video compact disc of the actual conduct of experiments and the materials for each experiment. In general, the perception of the teachers on the adequacy and adoptability of the Chemistry Laboratory Mini-Kit is not significantly affected by their personal profile and their school profile. However, it was found that significant differences on the perception of the respondents on the adequacy of the kit exist if they are grouped according to school location. Those who are from the barangays gave significantly higher ratings than those from towns and the city. A significant factor affecting the respondents',perception on the adequacy of the mini-kit is the number of regional seminars/trainings they attendedRegression analysis showed that as the number of regional seminars/trainings increased, the adequacy rating turned out to be lower. The integration ofthe Chemistry Laboratory Mini-Kit in Grade 7 Science instruction improved the learning of the students. Secondary school teachers, however, cited that the problem that they foresee is the unwillingness and inability of the students to bring household materials needed in some experiments. They also recommended some alternative materials to lessen the probable cost of the Chemistry Laboratory Mini-kit.